2013
DOI: 10.5194/isprsarchives-xl-1-w2-157-2013
|View full text |Cite
|
Sign up to set email alerts
|

Uav Photogrammetry: Block Triangulation Comparisons

Abstract: ABSTRACT:UAVs systems represent a flexible technology able to collect a big amount of high resolution information, both for metric and interpretation uses. In the frame of experimental tests carried out at Dept. ICA of Politecnico di Milano to validate vector-sensor systems and to assess metric accuracies of images acquired by UAVs, a block of photos taken by a fixed wing system is triangulated with several software. The test field is a rural area included in an Italian Park ("Parco Adda Nord"), useful to stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 8 publications
0
26
0
2
Order By: Relevance
“…The next phase of the work was the processing of the on site acquired data; the images of the different flights were processed in several blocks with the software Pix4D Mapper (Gini et al, 2013;Ostrowski & Hanus 2016;Rodrigues et al, 2016). As previously reported, we decided to use a specific product for our evaluations about the main topic of this article, then the processes of all the seven projects were stopped at the phase of point cloud generation (no other products such as meshes or ortophotos were created in this phase).…”
Section: Processing Workflow With Pix4dmentioning
confidence: 99%
“…The next phase of the work was the processing of the on site acquired data; the images of the different flights were processed in several blocks with the software Pix4D Mapper (Gini et al, 2013;Ostrowski & Hanus 2016;Rodrigues et al, 2016). As previously reported, we decided to use a specific product for our evaluations about the main topic of this article, then the processes of all the seven projects were stopped at the phase of point cloud generation (no other products such as meshes or ortophotos were created in this phase).…”
Section: Processing Workflow With Pix4dmentioning
confidence: 99%
“…PhotoScan was selected according to [37] and [38], who demonstrated that it provides the most reliable results among existing softwares based on Structure from Motion algorithms. For each flight, between 5 to 12 ground control points (GCP) were identified on the Google Earth image ( Figure 1) and used in PhotoScan to get the absolute coordinates of the DPC.…”
Section: Point Cloud Derived From Overlapping Rgb Imagesmentioning
confidence: 99%
“…무인항공사진측량의 정확도 수준이 기존의 전문적인 항 공사진측량에 버금가는지 여부에 관한 최근의 연구들은 확실한 결론을 내리지 못하고 있다 (Vallet et al 2011;Gini et al 2013;Colomina and Molina 2014 (Fig. 4(a)).…”
unclassified